Inhibition of Serine Proteases as a Novel Therapeutic Strategy for Abdominal Pain in IBS - Decraecker, Lisse; Boeckxstaens, Guy; Denadai-Souza, Alexandre (Frontiers in Physiology, 2022)
Serine proteases are heavily present in the gastrointestinal tract where they are essential in numerous physiological processes. An imbalance in the proteolytic activity is a central mechanism underlying abdominal pain in irritable bowel syndrome (IBS). Therefore, protease inhibitors are emerging as a promising therapeutic tool to manage abdominal pain in this functional gastrointestinal disorder. With this review, we provide an up-to-date overview of the implications of serine proteases in the development of abdominal pain in IBS, along with a critical assessment of the current developments and prospects of protease inhibitors as a therapeutic tool. In particular, we highlight the current knowledge gap concerning the identity of dysregulated serine proteases that are released by the rectal mucosa of IBS patients. Finally, we suggest a workflow with state-of-the-art techniques that will help address the knowledge gap, guiding future research towards the development of more effective and selective protease inhibitors to manage abdominal pain in IBS.